Engineering unsymmetrically coordinated Cu-S1N3 single atom sites with enhanced oxygen reduction activity - Huishan Shang (Nature Portfolio, 2020)
Engineering the coordination environment of single atom catalysts offers to opportunity to optimize electrocatalytic activity. In this work, the authors prepare an unsymmetrical Cu-S1N3 single atom site on porous carbon with high performance in the oxygen reduction reaction.